Talking About SOME and ALL: What Determines the Usage of Quantity-Denoting Expressions?. Issue 8 (17th November 2018) - Huang, Yi Ting; Arnold, Jennifer E.
ABSTRACT: Reference production is often studied through single dimensions of contrast (e.g., "tall glass" when there are one or two glasses of varying height). Yet real-world communication is rarely so simple, raising questions about the factors guiding more complex referents. The current study examines decisions to mention set relations (e.g., using quantity-denoting expressions like "some of the houses" to refer to two of five houses) versus object categories only (e.g., using bare plurals like "houses"). Two experiments used vignettes to vary discourse focus on objects (prominent vs. nonprominent) and scenes to vary the set type described (subset vs. total set). Speakers were more likely to communicate set relations of prominent objects, particularly when they elicit high name agreement in the case of total sets. Speakers' use of quantity-denoting expressions also increased listeners' sensitivity to set relations in an object-matching task. This suggests that unlike simpler forms of modification that often decrease with greater focus, quantity-denoting expressions provide additional information about the set relations of prominent referents.